Seasonal fluctuation of the citrus bud mite population with an improved spraying programme for lemon trees in view (Bollettino di zoologia agraria e bachicoltura, 2024)
The monthly fluctuations of Aceria sheldoni population were studiedon different citrus varieties at Eleonas in the Aegeon area. Growth cycles of thetrees and the seasonal climatic conditions affecting population size. The periodsof highest contraction of the population inside the buds and of dispersal aredetermined as well as the appropriate time to check the growth of the populationby intervention. Predator mites, including Phytoseiidae seem little effective incontrolling A. sheldoni.
Keywords: citrus; Aceria sheldoni; fluctuation population; Greece